2013
DOI: 10.4103/2141-9248.122123
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of patient waiting time in the general outpatient department of a tertiary health institution in North Western Nigeria

Abstract: Background:The amount of time a patient waits to be seen is one factor which affects utilization of healthcare services. Patients perceive long waiting times as barrier to actually obtaining services and keeping patients waiting unnecessarily can be a cause of stress for both patient and doctor.Aim:This study was aimed at assessing the determinants of patients’ waiting time in the general outpatient department (GOPD) of a tertiary health institution in northern Nigeria.Subjects and Methods:This descriptive cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 11 publications
4
51
0
1
Order By: Relevance
“…Several studies in low-, middle- and high-income countries support the notion that long waiting times can cause stress and dissatisfaction in patients [26–28]. Similar to our study, research conducted in northern Nigeria found that the main reason for long waiting times was an imbalance in demand and supply (large numbers of patients with few healthcare workers) [27]. Accordingly, it seems that long waiting times in hospitals are common in developing countries [29].…”
Section: Discussionsupporting
confidence: 87%
“…Several studies in low-, middle- and high-income countries support the notion that long waiting times can cause stress and dissatisfaction in patients [26–28]. Similar to our study, research conducted in northern Nigeria found that the main reason for long waiting times was an imbalance in demand and supply (large numbers of patients with few healthcare workers) [27]. Accordingly, it seems that long waiting times in hospitals are common in developing countries [29].…”
Section: Discussionsupporting
confidence: 87%
“…Research among women in Kampala revealed that the non-monetary costs of attending an HIV clinic visits such as a long waiting time to see a health worker led some people to choose fee for service options at nearby general clinics for conditions they otherwise would have sought care for free at their primary HIV treatment centre [ 11 ]. Studies in the US, as well as in Nigeria and Uganda suggest that delays at clinics cause customer dissatisfaction and convey a sense of poor service [ 12 – 14 ]. Payment for health services by the patient may counterbalance this, by allowing the patient to secure a specified set of healthcare services, at a specified level of quality and subject to a specified maximum level of personal inconvenience [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, quality is not only the outcome, especially from the patient perspective. Time spent waiting for connection is rarely enjoyed by patients [ 5 ], especially when there is uncertainty about the duration. Patients in the waiting room should know how long they have to wait, and this should not exceed a certain reasonable amount of time.…”
Section: Introductionmentioning
confidence: 99%